The scholarly journal Slavistica Vilnensis: Professor Valery Chekmonas Conception and its Embodiment (1995–2016) - Коницкая, Елена (Slavistica Vilnensis, 2018)
[full article, abstract in Russian; abstract in Lithuanian and English]This article presents the shaping of the concept of the international scientific review dedicated to Slavonic studies. This conception has been formed by professor Valery Chekmonas during the difficult period of independence restoration in Lithuania. For the first time, the concept was presented in the academic journal Kalbotyra (Linguistics) (2), which had been examining questions of Russian and Slavonic linguistics. This article shortly illustrates the origins of the scientific journal Slavistica Vilnensis. Its activities, when the executive editor of the review was V. Chekmonas, is widely examined. The further work of this academic journal (in years 2005–2016) is also publicized. The last period is presented as the phase of maintaining and developing the foundations that have been laid in 1995 and appeared as a coherent concept in 1997. This particular view enabled Slavistica Vilnensis to become an independent academic journal, incorporated into national and international databases, and occupy its rightful place amongst international Slavistic journals.
Keywords: Slavistica Vilnensis, Kalbotyra (2), prof. V. Chekmonas, Department of Slavic philology (VU), Concept of the scientific journal, Slavic philology